House dust mite sublingual tablet is effective and safe in patients with allergic rhinitis. Issue 3 (23rd August 2016) - Okamoto, Y.; Fujieda, S.; Okano, M.; Yoshida, Y.; Kakudo, S.; Masuyama, K.
Abstract: Background: House dust mite (HDM) is the major indoor allergen for allergic diseases such as allergic rhinitis (AR) and asthma. Although sublingual immunotherapy is a curative treatment for HDM‐induced AR, data from large‐scale studies are limited. We evaluated the efficacy and safety of HDM tablets in adolescent and adult patients (aged 12–64 years) with HDM‐induced AR with or without intermittent asthma. Methods: In a double‐blind trial in Japan, 968 subjects were randomized 1 : 1 : 1 to 300 index of reactivity (IR), 500 IR, or placebo groups. The primary endpoint was the Average Adjusted Symptom Score (AASS) in the last eight weeks of the 52‐week treatment. Secondary endpoints included individual nasal and ocular symptom scores, rescue medication use, and the Japanese Rhinoconjunctivitis Quality of Life Questionnaire (JRQLQ) scores. Results: The AASS in the last eight weeks of treatment significantly improved in both the 300 IR and the 500 IR groups compared to that in the placebo group ( P < 0.001). In the 300 IR group, the onset of action occurred at week 8–10. All four nasal symptoms significantly improved in both active treatment groups; rescue medication use and JRQLQ outcome improved in the 300 IR group. Most adverse events (AEs) were mild, and 16 serious AEs (SAEs) were reported; however, none of them were drug‐related. Conclusions: One‐year treatment with 300 IR and 500 IR HDM tablets was effective without major safety concerns. The recommended therapeutic dose for AR is 300 IR.